Influência da adição de vanádio nas propriedades mecânicas de aços médio teor de carbono para beneficiamento - Gustavo Levy Canaan (2007)
This work contributes to the understanding of the variation in the mechanical properties in all processes of the suspension springs production if the steel chemical composition have been modified. It studied the change in the chemical composition of high carbonsteel alloyed with Cr and Si through the vanadium addition working as a microalloying element. These processes include the wire rod production, the drawn bar fabrication and the suspension spring coiling in the quenched and tempered condition. This work evaluated the better conditions of the tempering treatment for this steel withmodified chemical composition to optimize the desired mechanical properties. The specimens were obtained in each single process of spring production and the mechanical properties and hardness properties were measured. The tempering treatment of the quenched samples was made in several temperatures to evaluate theoccurrence of secondary hardening. The tests were done in a comparative way, analyzing simultaneously the chemical composition modified steel and the standard chemical composition steel.Dilatometric tests were done in the specimens to measure the phase transformation temperatures and to better knowledge of the tempering process. The steel microstructure was characterized by optical microscopy and the fracture surfaces related to the different treatments were analyzed by stereoscopy and scanning electron microscopy (SEM), to characterize their macro and microscopic aspects, respectively, aiming to identify the fracture mechanisms related to the different conditions of thermal treatment. The results have shown that the vanadium addition is an effective method to improve the mechanical strength of the suspensions springs without ductility loss. So, it will be possible to produce these mechanical components with lower weight, reducing theautomobiles total weight, a request of the automotive industry.